Clinical characteristics of Lambert-Eaton myasthenic syndrome with positive P/Q-type voltage-gated calcium channel antibody - Tan, Y; Zhu, L; Wu, S; Ding, Q; Hu, Y; Wu, Y; Huang, Y; Li, K; Li, J; Guan, Y; Cui, L (Yiigle, 2021)
The clinical data of 18 patients diagnosed with Lambert-Eaton myasthenic syndrome (LEMS) from Department of Neurology of Peking Union Medical College Hospital from June 2016 to January 2018 were retrospectively analyzed and P/Q-type voltage-gated calcium channel (VGCC) antibodies were detected by radioimmunoprecipitation assay. The VGCC antibody (Ab)-positive rate of LEMS was 15/18, and there were no significant differences in gender, age, disease severity, and tumor prevalence. The disease course was shorter in the antibody-positive group (1.9 years vs 7.6 years, P=0.04), and the clinical manifestation was more complicated in the group with a higher VGCC-Ab. There was a significant correlation between VGCC-Ab and recurrence rate(τ=0.48, P=0.02).